Determinants of online shopping behavior of individuals during the COVID-19 pandemic in Tacloban City - Canillas, Febe Anne C.; Daban, Kayla Hanna J. (2022)
With the increasing trend of the internet nowadays, online shopping has made its way into the lives of people and managed to change the way people perceive the traditional method of shopping that involves physical appearance to shops. The COVID-19 pandemic has contributed to that change in consumers' behavior towards shopping. Thus, this study looked into the determinants of online shopping behavior during the COVID-19 pandemic based on the intention to practice online shopping. The participants of the study are online shoppers residing in Tacloban City. The data gathering was done through a survey using a self-administered questionnaire with a set of questions and utilizing a Google Form format disseminated through social media platforms. An online survey was conducted since face-to-face interaction was discouraged due to the COVID-19 risk. A convenience sampling techniques was used. Data analysis was based on the actual responses of the research participants. The research data is presented and interpreted in textual and tabular form along with descriptive statistics such as simple frequencies, percentages, measures of central tendency, and statistical tests, regression analysis. The Wilcoxon signed-ranks test showed that the COVID-19 pandemic elicited a statistically significant small effect on the expenditure of online shoppers in Tacloban City. Furthermore, findings revealed that age, marital status, monthly income, mobility restrictions, satisfaction level in terms of efficiency, homepage/application, online reviews and customer service, and the gadget accessories type of products had a significant influence on the online shopping behavior under the COVID-19 pandemic situation in the context of Tacloban City.